Mans mnemòniques en Y Ars demonstrativa de Ramon Llull. - ZAMORA, ANNA SERRA (Scripta)
This paper reviews the concept of the art of memory applied to the works of Ramon Llull through the introduction and commentary of the figures of hands with mnemonic, speculative, preaching goals. It is focused on the manuscripts of Ars demonstrativa --written in 1283-- dated between xiii and xvi century. In the manuscripts of Venice (Bibl. Marciana, Lat. VI. 200), Bergamo (MA 365) and San Candido (B. della Collegiata, VIII C.8), the hand is linked to figure S of Ars demonstrativa. In ms &.IV6 of El Escorial, the hand represents figure A. The most relevant precedent of this hand-shaped iconography is the Guidonian hand, in the field of music, but also figures of hands used for calendar calculation or meditation.